2015
DOI: 10.4274/vhd.36025
|View full text |Cite
|
Sign up to set email alerts
|

Occult Hepatitis B Reactivation After Chemoteraphy: A Case Report

Abstract: Occult hepatitis B virus (HBV) infection is defined as the detection of HBV genome in the liver and/or serum in HBsAg(-) individuals. Most patients with occult HBV infection are asymptomatic and are usually diagnosed during screening. Occult HBV infection is clinically significant because it spreads through blood transfusion and organ transplantation and triggers the reactivation of HBV in immunosuppressive patients. In this paper, we present a 63-year-old patient with occult hepatitis B who was scheduled for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In the recent issue of the Viral Hepatitis Journal, we read with interest the article by Uyanıkoglu et al (1), "Occult Hepatitis B Reactivation After Chemotherapy: A Case Report". In addition to this article, we wanted to emphasize a few additional important points about the subject.…”
Section: Dear Editormentioning
confidence: 98%
“…In the recent issue of the Viral Hepatitis Journal, we read with interest the article by Uyanıkoglu et al (1), "Occult Hepatitis B Reactivation After Chemotherapy: A Case Report". In addition to this article, we wanted to emphasize a few additional important points about the subject.…”
Section: Dear Editormentioning
confidence: 98%
“…HBVr is not limited to positive HBsAg patients. It also may develop during or after immunosuppressive therapy in patients with a positive antibody to the hepatitis B core antibody (anti-HBc) ( 30 - 32 ). Various studies reported clinical and virological reactivation in patients with OBI ( 30 , 31 ).…”
Section: Conditions With the Risk Of Hepatitis B Virus Reactivatiomentioning
confidence: 99%
“…It also may develop during or after immunosuppressive therapy in patients with a positive antibody to the hepatitis B core antibody (anti-HBc) ( 30 - 32 ). Various studies reported clinical and virological reactivation in patients with OBI ( 30 , 31 ). Furthermore, reports revealed that HBVr may also occur in resolved patients after immunosuppression ( 32 , 33 ).…”
Section: Conditions With the Risk Of Hepatitis B Virus Reactivatiomentioning
confidence: 99%